Avaliação de pellet feed de diferentes superfícies específicas como alternativa de matéria-prima para a sinterização de minério de ferro - Vinícius de Morais Oliveira (2019)
Recently, with the increase of the demand for iron ore and the depletion of high grade ore deposits, the main mining companies around the world have been investing to increase the use of low grade iron rocks, known as Itabirites. In Brazil, these rocks passed through a treatment process by classification, comminution and subsequent concentration. The product obtained is the pellet feed, a concentrate of high iron content, low level of contaminants, but very fine, typically 95% of the particles are smaller than 0.15 mm. Normally this material is used as raw material for the pelletizing process. However, due to its chemical quality it could also be used in sintering process. On the other hand, its small particle size negatively affects the permeability of this process, restricting its use to low quantities. In this way, different technological alternatives have been developed to allow the use of these materials in sintering, such as the use of intensive mixers, pre-agglomeration, use of special additives, mechanical treatment through roller press, among others. The mechanical treatment by roller press has been widely used to increase the specific surface of pellet feed used in the pelletizing process. Thus, this work aims to study the use of a natural pellet feed (as obtained after the concentration process in the mine) and mechanically treated in roller press with different specific surface levels as an alternative of raw material for sintering. On the first step of the work, 25% of traditional market sinter feed were replaced by natural and mechanically treated pellet feed. The iron ore mixtures were subjected to granulation tests for quasi-particles evaluation and pilot sintering to determine the effect of different pellet feed on productivity and metallurgical properties of the sinter. The results obtained showed that the increase of the specific surface of the pellet feed generally improves the agglomeration behavior (improvement of granulation index, improvement of quasi-particle formation and greater resistance), leading to better permeability allowing the recovery of productivity in pilot sintering without compromising the physical and metallurgical quality of the sinter produced. The minimum specific surface required for the pellet feed tested was between 1,400-1,500 cm2/g. The second part of the work was dedicated to granulation studies aiming to better understanding the mechanisms and phenomenology involved during this process step. In this case, the highest and the smallest specific surface pellet feed, their fractions smaller than 0.045 mm and the combination of these fractions with the same pellet feed were studied. Granulation Index (GI) results increased with the mean specific surface of the pellet feed and showed a stabilization at around 1,400-1,500 cm2/g. Similar trend was observed for quasi-particle strength, measured by the amount of fines of less than 0.15 mm that remained agglomerated to the quasi-particles. On the other hand, the optical microscopy analysis showed a continuous increase in the mean size of the quasi-particles and the thickness of the adherent layer with the average specific surface of pellet feed. The quasi-particles produced from the untreated pellet feed had a heterogeneous and poor consolidated adherent layer (some voids on it), leading to a lower GI and a low quasi-particle strength. On the the contrary, the quasi-particles produced by the highest specific surface pellet feed presented a better formation (homogeneous adherent layer and absence/smaller amount of voids), which contributed to a reasonable GI value with a good quasi-particle strength. In general, the mechanical treatment of the pellet feed promotes better granulation behavior of the ore mixture which positively affects the sintering process without compromising the physical and metallurgical quality of the produced sinter. Finally, a larger average quasi-particle size and a thicker adherent layer does not mean that there will be better agglomeration behavior of the mixture.